The efficacy and safety of intra-articular injection of corticosteroids in multimodal analgesic cocktails in total knee arthroplasty—a historically controlled study - Wang, Yixiong; Li, Zhichang; Gao, Xuan; Lin, Jianhao (Frontiers in Surgery, 2024)
Background Total knee arthroplasty (TKA) is a common and effective procedure. Optimizing pain control and reducing postoperative discomfort are essential for patient satisfaction. No studies have examined the safety and efficacy of intra-articular corticosteroid injections following TKA. This study aims to examine the safety and efficacy of corticosteroids in intra-articular multimodal analgesic injections. Materials and methods This was a historically controlled study conducted at a single academic institution. Before May 2019, patients received an intra-articular cocktail injection without corticosteroids during surgery, referred to as the non-corticosteroid (NC) group. After June 2019, intraoperatively, patients received an intra-articular cocktail injection containing corticosteroids, referred to as the corticosteroid (C) group. Finally, 738 patients were evaluated, 370 in the C cohort and 368 in the NC cohort. The mean follow-up duration was 30.4 months for the C group and 48.4 months for the NC group. Results The mean VAS scores at rest on postoperative day (POD) 1 (2.35) and POD3 (3.88) were significantly lower in the C group than those in the NC group, which were 2.86 (POD1) and 5.26 (POD3) (p < 0.05). Walking pain in the C group (4.42) was also significantly lower than that (5.96) in the NC group on POD3 (p < 0.05). Patients in the C group had a significantly higher mean range of motion (ROM) (92.55) on POD3 than that (86.38) in the NC group. The mean time to straight leg raise for group C (2.77) was significantly shorter than that (3.61) for the NC group (p < 0.05). The C group also had significantly fewer rescue morphine (1.9) and metoclopramide (0.21) uses per patient than the NC group, which were 3.1 and 0.24, respectively. No significant differences in fever or vomiting rates between groups were found. Patients in neither group developed periprosthetic joint infections or skin necrosis. One patient in the C group suffered from wound dehiscence, and the wound healed well after debridement. No patient died or had a re-operation in either group. Conclusions This pilot trial found that intra-articular injection of multimodal analgesia (including corticosteroids) reduced initial postoperative pain, increased ROM in the early postoperative days (up to POD3), and did not increase wound complications or infection rates in approximately 30 months of follow-up.